EFEKTIVITAS SUPLEMENTASI VITAMIN A DOSIS TINGGI TERHADAP TINGKAT PENYEMBUHAN DAN STATUS IMUN ANAK BALITA PENDERITA TUBERKULOSIS PARU - Susi S. Suwardi; Ance Murdiana; Muhilal Muhilal; Endi Ridwan; Effendi Rustan; Susilowati Herman; Sri Martuti; Tita Miawati (Persagi, 1999)
Effectiveness of High Dose Vitamin A Supplementation on The Recovery Rate and Immune Status of Underfive Children Suffering From Tuberculosis.Tuberculosis (TB), the infectious disease, is still one of the health problems in Indonesia. TB does not just make the people sick physically, but also interfere the immunity. As we have known that vitamin A can improve the immunity. The aimed of this randomized double blind study was to know the effect of high dose vitamin A on the improvement, immune status and the relationship between vitamin A and immune status in TB. Sixtyfive underfive children were selected from the Pediatrics Wards for out patient in Salak and Clsarua Hospital. They were grouped into 11 treatment group who received standard regimen therapy for TB plus high dose vitamin A in each month for 6 months and 21 control group who received the same TB regimen plus placebo also in each month for 6 months. Data on physical examination, weight, height, hemoglobin (Hb), hematocrit (Ht), blood sedimen rate (BSR), serum vitamin A, immunoglobulin G (IgG) to TB, chest X ray (CXR) and food consumption were collected before and after (6 months) intervention. Information on morbidity and socioeconomic also were recorded. To evaluate the degree of improvement, score on nutritional status, BSR and CXR were made. The results showed that after 6 month there were improvement in anthropometry status, morbidity rate, Hb, Ht, BSR, IgG and CXR for both groups. The treatment group was improved in 7.2% subjects meanwhile the control group was improved in 58% subjects. Analysis for scoring improvement showed that the treatment group had better improvement 2,4 times than the control group. The conclusions are that the high dose vitamin A has a positive effect on the recovery and immune status of underfive children suffering TB. This study suggests to give high dose vitamin A to the regimen therapy for TB in children to get better results.Keywords: tuberculosis, vitamin A supplementation, IgG, recovery rate.